2021
DOI: 10.1111/jipb.13062
|View full text |Cite
|
Sign up to set email alerts
|

Mediator tail module subunits MED16 and MED25 differentially regulate abscisic acid signaling in Arabidopsis

Abstract: MED25 has been implicated as a negative regulator of the abscisic acid (ABA) signaling pathway. However, it is unclear whether other Mediator subunits could associate with MED25 to participate in the ABA response. Here, we used affinity purification followed by mass spectrometry to uncover Mediator subunits that associate with MED25 in transgenic plants. We found that at least 26 Mediator subunits, belonging to the head, middle, tail, and CDK8 kinase modules, were co‐purified with MED25 in vivo. Interestingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Given that cell suspension cultures were used in the previous study (Backstrom et al, 2007) and seedlings were used in the current study, it is possible that the kinase module functions as a part of MEDIATOR in seedlings but not in cell suspension cultures. The inclusion of the kinase module in the Arabidopsis MEDIATOR complex was also supported by an independent study published in this issue (Guo et al, 2020), but the study did not identify CYCC1-1, CYCC1-2, MED30, MED31, HAC1, and HAC5 as subunits of the MEDIATOR complex in Arabidopsis.…”
Section: Discussionmentioning
confidence: 90%
“…Given that cell suspension cultures were used in the previous study (Backstrom et al, 2007) and seedlings were used in the current study, it is possible that the kinase module functions as a part of MEDIATOR in seedlings but not in cell suspension cultures. The inclusion of the kinase module in the Arabidopsis MEDIATOR complex was also supported by an independent study published in this issue (Guo et al, 2020), but the study did not identify CYCC1-1, CYCC1-2, MED30, MED31, HAC1, and HAC5 as subunits of the MEDIATOR complex in Arabidopsis.…”
Section: Discussionmentioning
confidence: 90%
“…All Arabidopsis thaliana mutants and transgenic plants used were in the Columbia‐0 (Col‐0) ecotype background. siz1‐2 (SALK_065397), stop1 (SALK_114108), almt1 (SALK_ 009629), and med16‐2 (SALK_048091) are previously reported T‐DNA insertion mutants (Miura et al, 2005; Liu et al, 2009; Sawaki et al, 2009; Guo et al, 2020b) and sfr6‐1 carries a ethylmethane sulfonate (EMS)‐induced mutation of MED16 (Knight et al, 2009). The s iz1‐2/stop1 and siz1‐2/almt1 mutants were derived by crossing siz1‐2 with stop1 or almt1 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was found that MED16 interacts with ABI5 and positively affects ABA signalling (Guo et al . 2021). Gain‐ and loss‐of‐function studies demonstrated that EIN3/EIL1 is also necessary and sufficient for enhanced salt tolerance (Peng et al .…”
Section: Common Players In Aba Drought/salt Stress and Fe Deficiency Signallingmentioning
confidence: 99%